Trunk extensor and flexor strength capacity in healthy young elite athletes aged 11-15 years - Mueller, J.; Mueller, S.; Stoll, J.; Baur, H.; Mayer, F. (The Journal of Strength and Conditioning Research, 2014)
Differences in trunk strength capacity because of gender and sports are well documented in adults. In contrast, data concerning young athletes are sparse. The purpose of this study was to assess the maximum trunk strength of adolescent athletes and to investigate differences between genders and age groups. A total of 520 young athletes were recruited. Finally, 377 (n = 233/144 M/F; 13 ± 1 years; 1.62 ± 0.11 m height; 51 ± 12 kg mass; training: 4.5 ± 2.6 years; training sessions/week: 4.3 ± 3.0; various sports) young athletes were included in the final data analysis. Furthermore, 5 age groups were differentiated (age groups: 11, 12, 13, 14, and 15 years; n = 90, 150, 42, 43, and 52, respectively). Maximum strength of trunk flexors (Flex) and extensors (Ext) was assessed in all subjects during isokinetic concentric measurements (60°/s; 5 repetitions; range of motion: 55°). Maximum strength was characterized by absolute peak torque (Flexabs, Extabs; Nm), peak torque normalized to body weight (Flexnorm, Extnorm; N·m/kg BW), and Flexabs/Extabs ratio (RKquot). Descriptive data analysis (mean ± SD) was completed, followed by analysis of variance (a = 0.05; post hoc test [Tukey-Kramer]). Mean maximum strength for all athletes was 97 ± 34 Nm in Flexabs and 140 ± 50 N·m in Extabs (Flexnorm = 1.9 ± 0.3 Nm/kg BW, Extnorm = 2.8 ± 0.6 N·m/kg BW). Males showed statistically significant higher absolute and normalized values compared with females (p < 0.001). Flexabs and Extabs rose with increasing age almost 2-fold for males and females (Flexabs, Extabs: p < 0.001). Flexnorm and Extnorm increased with age for males (p < 0.001), however, not for females (Flexnorm: p = 0.26; Extnorm: p = 0.20). RKquot (mean ± SD: 0.71 ± 0.16) did not reveal any differences regarding age (p = 0.87) or gender (p = 0.43). In adolescent athletes, maximum trunk strength must be discussed in a gender- and age-specific context. The Flexabs/Extabs ratio revealed extensor dominance, which seems to be independent of age and gender. The values assessed may serve as a basis to evaluate and discuss trunk strength in athletes.